LVIS-within-enterprise double-stent technique with coil embolization in the treatment of patients with acutely ruptured intracranial vertebrobasilar artery-dissecting aneurysms - Wu, Qiaowei; Meng, Yuxiao; Chen, Aixia; Xu, Shancai; Wang, Chunlei; Ji, Zhiyong; Qi, Jingtao; Yuan, Kaikun; Shao, Jiang; Shi, Huaizhang; Wu, Pei (Frontiers in Neurology, 2023)
Objective: To evaluate the feasibility of LVIS within Enterprise double stent technique for patients with acutely ruptured intracranial vertebrobasilar dissecting aneurysms (ari-VBDAs). Methods: A total of 30 patients with ari-VBDAs underwent reconstructive treatment using LVIS within enterprise double stent technique with coil embolization between January 2014 to May 2022 were retrospectively enrolled. Patients’ characteristics, clinical and imaging outcomes were reviewed. The functional outcomes were assessed using the modified Rankin Scale (mRS). Results: A total of 34 ari-VBDAs were identified, including 7 (20.6%) basilar artery aneurysms and 27 (79.4%) vertebral artery aneurysms. All aneurysms were successfully treated in the acute phase. Six (20.0%) patients experienced in-hospital serious adverse events, including 2 deaths (6.7%). The median clinical follow-up time of the remaining 28 patients was 20.0 (IQR, 7.3-40.8) months. The incidences of dependency or death (mRS score of 3-6) at discharge and at last follow-up were 16.7% and 14.3%, respectively. Aneurysm rebleeding occurred in 1 (3.3%) patient periprocedurally. Three (10.0%) patients had ischemic events, 1 of which occurred during the periprocedural period and 2 during follow-up. Two patients (6.7%) underwent ventriculoperitoneal shunt. Imaging follow-up was available for 14 patients at the median of 12 (IQR, 7.0-12.3) months, with a complete occlusion rate of 93.3% (14/15). One patient experienced parent artery occlusion, and no aneurysm recanalized. Conclusion: LVIS within enterprise double stent technique with coil embolization for the treatment of ari-VBDAs could be performed with good safety profile and high technical success rate. The rate of complete aneurysm occlusion during follow-up seemed to be satisfactory.